Pengaruh Penerapan Teaching Factory Untuk Meningkatkan Kompetensi Dan Jiwa Kewirausahaan Siswa SMKN 10 Luwu - Nadirah; Kamaruddin, Syamsu A. (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2024)
In efforts to create strong entrepreneurs, the world of education, in this case vocational schools, is one of the institutions that has a very important role. Empirical facts show that the majority of vocational school graduates do not meet the needs or demands of stakeholders. Graduates tend to be "job seekers" and not many are able to work "independently". To overcome this problem, the policy made by the Indonesian government is to improve the quality of human resources through education, instill an entrepreneurial spirit at every level and level of education, and try to expand employment opportunities. one of the strategies created is to implement a teaching factory or industrial teaching program in vocational schools. This research applies library research, namely the method used by collecting data. Teaching factory is a development of a production unit and dual education system that has been implemented in vocational schools. The teaching factory concept is a form of development from a vocational school to a production school model. Teaching factories have several objectives, namely increasing the competency of vocational school graduates, increasing the entrepreneurial spirit of vocational school graduates and producing products in the form of goods or services that have added value. Teaching factories as a means of learning are quite effective in increasing students' competence and entrepreneurial spirit, so that teaching factories can If it runs well and is able to achieve the expected goals, it requires cooperation and assistance from various parties involved in it